Isohexide-diacetal based polymers and a process thereof - Chikkali, Samir H.; Rajput, Bhausaheb S. (WO/2014/181358, 2014)
The present invention discloses isohexide based compounds and their polymers which are derived from renewable resources and are potentially degradable. Also disclosed herein is the synthesis of isohexide based monomers and their polymers from renewable resources which are potentially degradable. Further, the present invention disclose a process for the synthesis of isohexide based copolymers via copolymerization of isohexide based monomers and long chain diols, which are degradable. (FR)Cette invention concerne des composés à base d'isohexide et leurs polymères qui sont dérivés de ressources renouvelables et sont potentiellement dégradables. Cette invention concerne également la synthèse de monomères à base d'isohexide et leurs polymères à partir de ressources renouvelables qui sont potentiellement dégradables. Un procédé de synthèse de copolymères à base d'isohexide par copolymérisation desdits monomères à base d'isohexide et de diols à chaîne longue, qui sont dégradables, est en outre décrit.